NOVEL NETWORK STEGANOGRAPHY APPROACHES FOR CONFIDENTIAL TRANSMISSION OF INFORMATION - Karadogan, Ismail; Das, Resul; Karci, Ali (Ieee, 2017)
In this paper, two different packet timing and IP ID based network steganography approaches have been proposed to provide confidential transmission of information. In the proposed packet timing approach, it is seen that the bandwidth is higher than the previous methods. The proposed IP ID field based approach has been found to be more effective than previous methods in ensuring the uniqueness of the ID field and is suitable for sending confidential data over the Internet. In addition, comprehensive information on this study was presented by examining methods of information hiding, hidden channels and secret data transmission in the network environment.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Network steganography; covert channels; network security; communication protocols